The Effect of Universal Health Care on the Out-Of-Pocket Health Expenditures: Evidence from a Natural Experiment - Muhammad Asali; Valida Pantsulaia (Institute of Labor Economics (IZA), 2022)
In the first two quarters of 2013 the Georgian government introduced and fully implemented a universal health care (UHC) plan covering all those not-yet publicly or privately insured. We estimate the effect of the introduction of the universal healthcare plan on the level of out-of-pocket (OOP) health expenditures of households. We find that the program saved households an economically and statistically significant amount of 92 GEL per household/ month: a major effect, amounting to about 10% of the average household monthly income and 30% of the average individual monthly income at the time. The OOP payments reduction is almost totally attributed to people utilizing serious, emergency, or life-saving inpatient and outpatient services—lending support to the hypothesis that the UHC program, not only has reduced the OOP health expenditures, but it might have also improved the overall health status in the country.
Keywords: I13; I18; H51; 330; universal healthcare; out of pocket health expenditures; public health; health insurance